2012
DOI: 10.1016/j.jsat.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment program ownership, Medicaid acceptance, and service provision

Abstract: The Institute of Medicine noted that effective substance abuse treatment (SAT) programs integrate individual therapeutic approaches with transitional/ancillary services. In addition, research suggests that type of ownership impacts SAT services offered and that Medicaid plays a key role in SAT access. Data from the National Survey of Substance Abuse Treatment Services for the years 2000 and 2002-2006 were used to examine relationships among SAT program Medicaid acceptance, program ownership, and transitional/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…This suggests that programs accepting Medicaid for SA treatment services may have more of a quality orientation by virtue of the fact that they have taken the extra step of obtaining national accreditation or licensure/certification—an entirely voluntary step found to relate to higher odds of offering wrap‐around and continuing care services, all associated with improved long‐term SA treatment outcomes (Chriqui et al 2007). The increased likelihood of Medicaid acceptance at programs with large client counts is in line with previously discussed studies (Cunningham and May 2006), and increased Medicaid acceptance at government and not‐for‐profit program cases (versus for‐profit) is in line with findings related to decreasing private funding of SA treatment (Levit et al 2008) and other ongoing research (McBride et al 2008). Decreased Medicaid acceptance at private, for‐profit programs may also help explain research finding decreased initial SA treatment access and shorter stays in treatment for clients unable to pay (Friedmann et al 2003; Nahra, Alexander, and Pollack 2009).…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that programs accepting Medicaid for SA treatment services may have more of a quality orientation by virtue of the fact that they have taken the extra step of obtaining national accreditation or licensure/certification—an entirely voluntary step found to relate to higher odds of offering wrap‐around and continuing care services, all associated with improved long‐term SA treatment outcomes (Chriqui et al 2007). The increased likelihood of Medicaid acceptance at programs with large client counts is in line with previously discussed studies (Cunningham and May 2006), and increased Medicaid acceptance at government and not‐for‐profit program cases (versus for‐profit) is in line with findings related to decreasing private funding of SA treatment (Levit et al 2008) and other ongoing research (McBride et al 2008). Decreased Medicaid acceptance at private, for‐profit programs may also help explain research finding decreased initial SA treatment access and shorter stays in treatment for clients unable to pay (Friedmann et al 2003; Nahra, Alexander, and Pollack 2009).…”
Section: Discussionsupporting
confidence: 87%
“…Researchers report that for-profit treatment facilities are less likely to serve poorer clients and offer key ancillary/transitional services than nonprofits. [ 14 ] For India, the GO and NGO sector appear to be serving an important part in increasing access to treatment for the poor and providing the extent of treatment services required by the vulnerable drug-using population. The GO sector is an important treatment provider, and the NGO sector has the flexibility and access to most vulnerable population at the community level.…”
Section: Discussionmentioning
confidence: 99%
“…Substance abuse counselors may lack expertise to focus on issues related to partner violence, or their high caseloads may prevent them from devoting time to effective screening for domestic violence. Leadership issues, high clinician turnover, lack of administrative support and resources for staff training, and issues with the funding stream may also be barriers to concurrently treating domestic violence and substance abuse (14,26).…”
Section: Discussionmentioning
confidence: 99%
“…Covariates were selected on the basis of factors used in previous studies of the N-SSATS and factors that have been empirically shown to affect substance abuse treatment services (26)(27)(28). They were primary treatment focus (substance abuse, mental health, mix of mental health and substance abuse, general health care, or other); private versus government ownership; facility region (Northeast, Midwest, South, West, or U.S. jurisdiction or territory); hospital location; provision of standard case review with a quality review committee; treatment in language other than English; provision of nonhospital residential substance abuse treatment; provision of regular outpatient treatment; use of a sliding fee scale or treatment free of charge; Medicare reimbursement accepted; Medicaid reimbursement accepted; receipt of federal, state, county, or local funds (yes or no); and licensed or certified by a state substance abuse agency, mental health department, state health department, or hospital authority (one response selected).…”
Section: Covariatesmentioning
confidence: 99%